Revista Fundação JP: dilemas do desenvolvimento e do planejamento na década de 1970 em Minas Gerais (Revista de História Regional, 2023)
The present paper is part of the literature that has resumed the experiences and institutionalities about urban-regional planning during the Brazilian civil-military dictatorship. Here, the Revista Fundação JP is studied, edited by Fundação João Pinheiro (FJP) – an institution created in 1969 to produce studies and statistics that would help the development of Minas Gerais – during the 1970s, when the theme was organized and consolidated in the state apparatus of Minas Gerais. The study of publications on the theme of planning and development in Revista Fundação JP is illustrative, as it demonstrates the changes in focus given the Minas Gerais and national context, the plurality of theoretical-methodological references and the debates about the paths taken. Thus, its study helps in understanding the processes of institutional consolidation of issues of planning and state action within the scope of urban and regional policies.
Keywords: Urban-Regional Planning; Minas Gerais; JP Foundation Journal; Development; Institutions